Assessment of the Dual Role of Clumping Factor A in S. Aureus Adhesion to Endothelium in Absence and Presence of Plasma - Claes, Jorien; Ditkowski, Bartosz; Liesenborghs, Laurens; Veloso, Tiago Rafael; Entenza, Jose M.; Moreillon, Philippe; Vanassche, Thomas; Verhamme, Peter; Hoylaerts, Marc F.; Heying, Ruth (Thrombosis and Haemostasis, 2018)
Adhesion of Staphylococcus aureus to endothelial cells (ECs) is paramount in infective endocarditis. Bacterial proteins such as clumping factor A (ClfA) and fibronectin binding protein A (FnbpA) mediate adhesion to EC surface molecules and (sub)endothelial matrix proteins including fibrinogen (Fg), fibrin, fibronectin (Fn) and von Willebrand factor (vWF). We studied the influence of shear flow and plasma on the binding of ClfA and FnbpA (including its sub-domains A, A16+, ABC, CD) to coverslip-coated vWF, Fg/fibrin, Fn or confluent ECs, making use of Lactococcus lactis, expressing these adhesins heterologously. Global adherence profiles were similar in static and flow conditions. In the absence of plasma, L. lactis-clfA binding to Fg increased with shear forces, whereas binding to fibrin did not. The degree of adhesion of L. lactis-fnbpA to EC-bound Fn and of L. lactis-clfA to EC-bound Fg, furthermore, was similar to that of L. lactis-clfA to coated vWF domain A1, in the presence of vWF-binding protein (vWbp). Yet, in plasma, L. lactis-clfA adherence to activated EC-vWF/vWbp dropped over 10 minutes by 80% due to vWF-hydrolysis by a disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13 and that of L. lactis-fnbpA likewise by > 70% compared to the adhesion in absence of plasma. In contrast, plasma Fg supported high L. lactis-clfA binding to resting and activated ECs. Or, in plasma S. aureus adhesion to active endothelium occurs mainly via two complementary pathways: a rapid but short-lived vWF/vWbp pathway and a stable integrin-coupled Fg-pathway. Hence, the pharmacological inhibition of ClfA-Fg interactions may constitute a valuable additive treatment in infective endocarditis.
Keywords: infective endocarditis; clumping factor A; fibronectin binding proteins; S. aureus; von Willebrand factor; fibrinogen; fibronectin